Activation of the NLRP3 inflammasome complex is not required for stress-induced death of pancreatic islets. - Jibran A Wali; Esteban N Gurzov; Stacey Fynch; Lorraine Elkerbout; Thomas W Kay; Seth L Masters; Helen E Thomas (PLoS ONE, 2014)
Loss of pancreatic beta cells is a feature of type-2 diabetes. High glucose concentrations induce endoplasmic reticulum (ER) and oxidative stress-mediated apoptosis of islet cells in vitro. ER stress, oxidative stress and high glucose concentrations may also activate the NLRP3 inflammasome leading to interleukin (IL)-1β production and caspase-1 dependent pyroptosis. However, whether IL-1β or intrinsic NLRP3 inflammasome activation contributes to beta cell death is controversial. This possibility was examined in mouse islets. Exposure of islets lacking functional NLRP3 or caspase-1 to H2O2, rotenone or thapsigargin induced similar cell death as in wild-type islets. This suggests that oxidative or ER stress do not cause inflammasome-mediated cell death. Similarly, deficiency of NLRP3 inflammasome components did not provide any protection from glucose, ribose or gluco-lipotoxicity. Finally, genetic activation of NLRP3 specifically in beta cells did not increase IL-1β production or cell death, even in response to glucolipotoxicity. Overall, our results show that glucose-, ER stress- or oxidative stress-induced cell death in islet cells is not dependent on intrinsic activation of the NLRP3 inflammasome.